FAKTOR PENYEBAB RENDAHNYA KOMPETENSI KONSULTAN PENGAWAS PADA PROYEK GEDUNG PEMERINTAH JAMBI - Atthaariq, Wibowo; Mulyani, Rini; Khadavi, Khadavi (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
The competence of the supervisory engineer is an important point to achieve the success of the project completion which has an influence on the results of the construction project work according to plan. This study aims to identify the factors that cause the low competence of the supervisory consultant (Supervisor Engineer) in building construction projects in Jambi City. The research method used is a combination approach, combining qualitative and quantitative approaches by distributing questionnaires to respondents. Validity, reliability, KMO and Bartletts testing and factor analysis were carried out on the respondents' questionnaire answers. The results of the study showed that there were 6 factors that influenced the causes of the low competence of the supervisory consultant in the Jambi City government building construction project. These factors are human resource factors, satisfaction, work environment, communication, education and experience can affect the competence of field supervisors in Jambi City. The dominant factor that influences the low competence of field supervisors in the Jambi City government building construction project is the human resource factor with the variable of the limited number of field supervisors to the number of projects implemented and the percentage of variance value is 36.850%.